Pengaruh Instagram Marketing terhadap Keputusan Pembelian pada Donat Madu Cihanjuang - Dafitri, Shalsabilla (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2023)
Donat Madu Cihanjuang is a franchise company engaged as a food provider that has been established since 2010, with its main product being donuts. The purpose of this study was to determine the influence of Instagram marketing on purchasing decisions at Donat Madu Cihanjuang. This study used a purposive sampling method. The population in this study were Instagram followers @donatmaduindonesia or consumers who had made purchases at Donat Madu Cihanjuang with 100 respondents. The data in this study were processed using the SPSS 26 application. The results of this study indicate that Instagram marketing has an influence on purchasing decisions.